Taking lanthanides out of isolation: tuning the optical properties of metal–organic frameworks. Issue 16 (7th April 2020) - Anderson, Samantha L.; Tiana, Davide; Ireland, Christopher P.; Capano, Gloria; Fumanal, Maria; Gładysiak, Andrzej; Kampouri, Stavroula; Rahmanudin, Aiman; Guijarro, Néstor; Sivula, Kevin; Stylianou, Kyriakos C.; Smit, Berend
Abstract : Computational and experimental study into two families of lanthanide-based metal organic frameworks with the same ligand, tuned to have different structural and optical properties. Abstract : Metal organic frameworks (MOFs) are increasingly used in applications that rely on the optical and electronic properties of these materials. These applications require a fundamental understanding on how the structure of these materials, and in particular the electronic interactions of the metal node and organic linker, determines these properties. Herein, we report a combined experimental and computational study on two families of lanthanide-based MOFs: Ln-SION-1 and Ln-SION-2. Both comprise the same metal and ligand but with differing structural topologies. In the Ln-SION-2 series the optical absorption is dominated by the ligand and using different lanthanides has no impact on the absorption spectrum. The Ln-SION-1 series shows a completely different behavior in which the ligand and the metal node do interact electronically. By changing the lanthanide in Ln-SION-1, we were able to tune the optical absorption from the UV region to absorption that includes a large part of the visible region. For the early lanthanides we observe intraligand (electronic) transitions in the UV region, while for the late lanthanides a new band appears in the visible. DFT calculations showed that the new band in the visible originates in the spatial orbital overlap between the ligand and metal node. Our quantum calculations indicated that Ln-SION-1 with late lanthanides might be (photo)conductive. Experimentally, we confirm that these materials are weakly conductive and that with an appropriate co-catalysts they can generate hydrogen from a water solution using visible light. Our experimental and theoretical analysis provides fundamental insights for the rational design of Ln-MOFs with the desired optical and electronic properties.